Parametric analysis of corrugated plate by using ANSYS finite element software - Abbas, Hajer Satih (2013)
In this study, ANSYS finite element software is used to analyse unstiffened and stiffened trapezoidal and sinusoidal corrugated plates due to uniform distributed vertical load. Different boundary conditions of corrugated plate are considered. The results were compared with the mesh free Galerkin method found in literature to show the convergence and accuracy of ANSYS finite element analysis. The stiffened and unstiffened of trapezoidal and sinusoidal corrugated plate are model using 3D finite element with type of element is shell181. It is found that the results from ANSYS are in good agreement with solution by mesh free Galerkin method. The effectiveness of stiffener plate was found obvious to reduce the deflection. Many profiles of trapezoidal corrugated plate are also analyzed based on ANSYS finite element software in order to choose the optimum shape between them and carry greater loads with less deflection and stresses.